Reactive Diluent-Induced Trade-Offs: Unraveling the Interplay Between Resin Flow and Volatility for Multilayer GFRP Laminate - Kim, Mingyu; Kim, Jaehoo; Han, Tae Hee; Kim, Jaewoo (한국고분자학회 2025년도 춘계학술대회 연구논문 초록집 제50권 제1호, 2025)
The incorporation of reactive diluents is crucial for improving the processability and performance of GFRP in advanced applications. This study explores the effect of reactive diluent (styrene) content (0, 20, 40, and 60 wt%) on the mechanical and structural properties of GFRP fabricated via the VARTM process. At 20 wt%, the Charpy impact strength and interlaminar shear strength are maximized, with enhanced fiber-matrix bonding and minimized porosity. However, at 40-60 wt%, mechanical performance deteriorated, and porosity increased. RVE and FEA-based simulations were conducted to analyze the failure mechanism depending on the reactive diluent content. This findings indicate that while higher diluent content reduces resin viscosity, improving fiber impregnation, it also increases diluent volatility, leading to void formation at the fiber-matrix interface. This study provides a comprehensive evaluation of reactive diluent content effects on the GFRP performance.